INVESTIGATING ISLAMIC EDUCATION STUDENTS' INTEREST IN PURSUING HIGHER DEGREES DURING TIMES OF ECONOMIC RECESSION AT FACULTY OF EDUCATION AND TEACHER TRAINING, AR-RANIRY STATE ISLAMIC UNIVERSITY - Intan Najwa, Annisa; Muluk, Safrul (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2025)
Pursuing higher education is a multifaceted decision influenced by financial, social, and psychological factors. This study examines the interest of students at the Faculty of Education and Teacher Training, Ar-Raniry State Islamic University, in pursuing postgraduate education amid an economic recession. It focuses on a sample of 70 fourth-year undergraduate students. Using a quantitative descriptive research design, the data were collected through a structured questionnaire consisting of 10 yes/no questions and 10 Likert scale questions, which were analyzed using descriptive statistics. The results show that 77.1% of the respondents acknowledged that the economic recession influenced their educational choices, while 87.1% believed that obtaining a higher degree would improve their career prospects. Financial constraints were a major concern, with 55.7% reporting a decrease in their family's ability to pay for education, yet 82.9% reported relying on scholarships or financial aid as a critical factor in their decision-making process. Despite the economic challenges, 90% of students remained optimistic about overcoming financial barriers, driven by both intrinsic (51.4% motivated by personal and professional growth) and extrinsic (94% recognizing career benefits) motivations. Social and academic support also played a critical role, with 92.9% influenced by mentorship and 97.1% by encouragement from family and friends. Concerns about educational quality persisted, however, as 87.1% of students perceived the recession as hurting higher education institutions. These findings underscore the need for higher education institutions and policymakers to expand financial aid programs, improve academic mentoring, and align educational curricula with the demands of the broader labor market to ensure equitable access to higher education during times of economic instability.